Women’s Ethics and Language Style in Nineteenth-Century Canonical Novels: A Comparative Stylistic Analysis of Austen, Brontë, and Flaubert - Fitri Arniati; Mulyati; Amalia Wahyuni Mustakim (Journal of Vocational, Informatics and Computer Education, 2026)
Purpose – Nineteenth-century novels functioned not only as literary texts but also as ideological sites where morality, gender norms, and women’s ethical roles were constructed, negotiated, and contested. This makes stylistic analysis a productive approach for examining how literary language encodes women’s ethics in canonical fiction.This study examines how language style constructs, reinforces, and challenges the representation of women’s ethics in three nineteenth-century canonical novels and proposes its relevance for critical literacy Methods – This study employed a qualitative stylistic design to analyze Pride and Prejudice, Jane Eyre, and Madame Bovary. The analysis focused on metaphors, similes, irony, repetition, and narrative strategies. Metaphors were identified using MIPVU, narrative structure was examined through Genette’s narratological framework, and inter-coder reliability was calculated using Cohen’s κ on a 15% subset of the corpus Findings – The findings show that each novel foregrounds a distinct stylistic pattern. Austen predominantly uses social irony and domestic metaphor, Brontë emphasizes emotional simile, repetition, and internal focalization, and Flaubert relies heavily on narrative irony and descriptive narration. The inter-coder reliability ranged from κ = 0.77 to κ = 0.84, indicating substantial agreement across the coding categories. Across the corpus, irony and metaphor emerged as the most salient comparative features Research implications – The study also proposes a theoretically grounded instructional model for critical literacy development through structured stylistic annotation, LMS-based discussion, and evidence-based literary interpretation in digital or blended learning contexts Originality – The language style in nineteenth-century fiction functions not merely as an aesthetic device but as an ideological instrument that shapes and contests women’s ethics.